Effectiveness of E-Module Circulation System Based on 8E Learning Cycle on High School Student's Critical Thinking Ability - Rosiana, Yuni; Syafii, Wan; Putra, Riki Apriyandi; Futra, Dedi (Journal of Educational Sciences, 2023)
Critical thinking skills are skills students must have in the 21st century. These skills can improve analytical skills and make students think more carefully This study aims to determine the effect of circulation system e-module based on learning cycle 8e on high school students' critical thinking skills. This type of research is quasi-experimental, which consists of 2 classes, namely XI IPA 1 as the experimental class with treatment using e-module circulation system based on learning cycle 8e and XI IPA 2 as the control class, which uses conventional learning. Based on the results of the study, it was found that there was a significant effect of the circulation system e-module based on learning cycle 8e on students' critical thinking skills, where in the control class the average posttest score was far below the experimental class, which was 55.5 and the experimental class average posttest score was 69.5. Based on the results of hypothesis testing, a significant value (2 tailed) was obtained of 0.003 (p<0.05). The use of circulation system e-module based on learning cycle 8e has a positive effect on students' critical thinking skills.